Direct computation of stress intensity factors in finite element method. Issue 3 (4th May 2017) - Caicedo, J.; Portela, A.
Abstract: This paper is concerned with the direct computation of stress intensity factors (SIFs) in the finite element analysis of the mixed-mode deformation of homogeneous cracked plates. The direct computation of SIFs is a natural consequence of a regularisation procedure, introduced before the finite element analysis takes place that uses a singular particular solution of the crack problem to introduce the SIFs as additional problem primary unknowns. In this paper, the singular term of Williams' eigenexpansion, derived for a semi-infinite crack, is used to regularise the elastic field of an edge-cracked finite plate. Two cracked plates were analysed with this technique, in order to assess the accuracy and efficiency of the formulation. The results obtained in this work are in perfect agreement with those obtained with the dual boundary element method and other published results. The accuracy and efficiency of the implementation described herein make this a reliable and robust formulation, ideal for the study of crack-growth problems, with the finite element method.